Left-sided gallbladder without situs inversus : report of a case - Ozsoy, Mehmet Sait; Buyuker, Fatih; Gapbarov, Aman; Colapkulu, Nuray; Erol, Cem Ilgin; Ekıncı, Ozgur; Eren, Tunc; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2018)
A gallbladder that is placed on the left side of the liver without situs inversus is a very rare situation. This anatomical position makes harder to define with ultrasonography (US) before operation. A 41-years-old woman admitted with complaints of indigestion, bloating and stomach pain which started one year ago. Multiple millimetric gall stones were detected at ultrasonography, and there wasn’t any information about the anatomic position of the gallbladder. A laparoscopic cholecystectomy was scheduled for the patient. It was visualized that the gallbladder was embedded in the segment III of the liver intraoperatively. In such cases, the fact that vascular and biliary anomalies may accompany should be kept in mind as this condition may hinder the clear visualization of the cystic artery and duct which may bring the risk of iatrogenic injury. International Journal of Human and Health Sciences Vol. 02 No. 03 July’18. Page : 158-160